Study Korelasi Hasil Belajar Kognitif dan Afektif Pembelajaran Tematik Muatan PPKn dan IPS pada Siswa Kelas V SDN Wukirsari - Wartono; Puspa Djuwita; Bambang Parmadi (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
The type of research used is quantitative research and the research method used is the correlational method. Correlational research aims to show whether or not there is a relationship between the variables studied by analyzing the affective and cognitive learning outcomes of Civics learning content and social studies learning content. The data analysis technique used is the correlation coefficient technique by correlating the rxy value with the r table value. From the results of the study it is known that there is a correlation/relationship between cognitive - affective learning outcomes in PPKn and IPS content in fifth grade students at SD Negeri Wukirsari. Correlation coefficient (rxy) between tables at a significant level of 5%. Cognitive and affective learning outcomes of PPKn content, rxy¬ = 0.970 > r table 0.05 = 0.320 r table is smaller than rxy and Sig.(2-tailed) 0.000 <0.005 reject Ho accept Ha with a high level of interpretation. Cognitive and affective learning outcomes of IPS content, rxy¬ = 0.871 > r table 0.05 = 0.320 r table is smaller than rxy and Sig.(2-tailed) 0.000 <0.005 reject Ho accept Ha with a high level of interpretation. The affective learning outcomes of PPKn content and IPS content, rxy¬ = 0.983 > r table 0.05 = 0.320 r table is smaller than rxy and Sig.(2-tailed) 0.000 <0.005 reject Ho accept Ha with a high level of interpretation. Cognitive learning outcomes of PPKn content and IPS content, rxy¬ = 0.983 > r table 0.05 = 0.320 r table is smaller than rxy and Sig.(2-tailed) 0.000 < 0.005 reject Ho accept Ha with a high level of interpretation.